If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5x + -10) = 67 Reorder the terms: (-10 + 5x) = 67 Remove parenthesis around (-10 + 5x) -10 + 5x = 67 Solving -10 + 5x = 67 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + 5x = 67 + 10 Combine like terms: -10 + 10 = 0 0 + 5x = 67 + 10 5x = 67 + 10 Combine like terms: 67 + 10 = 77 5x = 77 Divide each side by '5'. x = 15.4 Simplifying x = 15.4
| 34.5=z/70 | | 3m-2w=11 | | 374=m-23 | | 7a+60=25 | | -y=-x-3 | | n-7.75=18.5 | | 8d+7=-4(-2d-4) | | 4+3+8x=15 | | 17-11=3(x-4) | | 4-8g=10+g | | 5(x-16)=x-20 | | 2x^2-1=120 | | -3d+7=-9 | | 3/2x-4=12 | | -49+2x=23 | | ln(2y)=x | | 2x(y)=76 | | -8=3(k-7) | | 4+13=5 | | 2x+y=76+y | | g+242=79 | | 6x+4(-7x+6)=-130 | | a-4a=3a+1 | | -3.1x-7=-2.2x+2 | | 5000=2x+300 | | 2x(x-y)= | | 14x-65=73+17x | | 28.96+b=57.39 | | -419+6x=-9x+196 | | 57=2h | | 9=w-35 | | (2x-7)(-4x+18)=-24x+100 |